Treatment of Low HDL‐C Subjects with the CETP Modulator Dalcetrapib Increases Plasma Campesterol Only in Those Without ABCA1 and/or ApoA1 Mutations. Issue 12 (4th October 2014) - Niesor, Eric J.; Kallend, David; Bentley, Darren; Kastelein, John J. P.; Kees Hovingh, G.; Stroes, Erik S. G.
Abstract: We investigated the effect of dalcetrapib treatment on phytosterol levels in patients with familial combined hyperlipidemia (FCH) or familial hypoalphalipoproteinemia (FHA) due to mutations in apolipoprotein A1 ( ApoA1 ) or ATP‐binding cassette transporter A1 ( ABCA1 ). Patients ( n = 40) with FCH or FHA received dalcetrapib 600 mg or placebo in this 4‐week, double‐blind, crossover study. Lipids, apolipoproteins, cholesteryl ester transfer protein (CETP) activity and mass, and phytosterols were assessed. Dalcetrapib increased high‐density lipoprotein cholesterol (HDL‐C) and ApoA1 levels to a similar extent in FHA (+22.8, +13.9 %) and FCH (+18.4, +12.1 %), both p < 0.001 vs. placebo. Changes in CETP activity and mass were comparable for FHA (−31.5, +120.9 %) and FCH (−26.6, +111.9 %), both p < 0.0001 vs. placebo. Campesterol and lathosterol were unchanged in FHA (+3.8, +3.0 %), but only campesterol was markedly increased in FCH (+25.0 %, p < 0.0001 vs. placebo). Campesterol increased with dalcetrapib treatment in FCH but not in FHA, despite comparable HDL‐C and ApoA1 increases, suggesting that ApoA1 and/or ABCA1 is essential for HDL lipidation by enterocytes in humans.